A review on disability studies from 2000 To 2020 - R., Roshini; V., Rajasekaran; Mani, Manimangai (M. S. Thirumalai, 2021)
The purpose of this paper is to review some research articles related to disability that have been published so far. These reviews aim at throwing light on the changes in the perspective of the society, in any, towards disability and disabled people. The selected articles do not restrict themselves to any particular type of disability; rather, it gives an overview of disability discourses that have been discussed off late in academia.